Cleopatra : a life - Schiff, Stacy (New York : Little, Brown and Co., 2010)
The Pulitzer Prize-winning biographer brings to life one of the most intriguing woman in the history of the world: Cleopatra, the last queen of Egypt. Though her life spanned fewer than 40 years, it reshaped the contours of the ancient world.
That Egyptian woman -- Dead men don't bite -- Cleopatra captures the old man by magic -- The golden age never was the present age -- Man is by nature a political creature -- We must often shift the sails when we wish to arrive in port -- An object of gossip for the whole world -- Illicit affairs and bastard children -- The wickedest woman in history.
Includes bibliographical references (p. 347-349) and index.
Keywords: Cleopatra, -- Queen of Egypt, -- -30 B.C.; Queens -- Egypt -- Biography; Egypt -- Kings and rulers -- Biography; Egypt -- History -- 332-30 B.C.